PENGARUH KUALITAS LINGKUNGAN FISIK UDARA TERHADAP ANGKA KUMAN DI RUMAH SAKIT - Susilawati, Susilawati; Ilham, Ilham; Guspianto, Guspianto (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2021)
ABSTRACT Around 9% or 1.4 million inpatients in hospitals in the world experience nosocomial infections due to germ exposure related with the hospital's physical environment condition. This study aims to analyze the effect of the air physical environment in the in-patient room at HAMBA Hospital, Muara Bulian, Jambi. A quantitative study has been conducted with a cross sectional design with 30 samples of in-patient rooms. Data collected by measuring directly includes microbial density rate, temperature, humidity, lighting and dust, and analyzed using the Kendall-Tau correlation test. The results showed that all the air physical environmental factors had effect on microba rate, including temperature (p = 0.020), humidity (p = 0.000), lighting (p = 0.004) and dust (p = 0.001). It is especially recommended for hospitals to pay attention to the condition of inpatient rooms in order to minimize the growth of micro-organisms that cause nosocomial infections by opening windows every morning, cleaning the air conditioner at least every 6 months, changing curtains with bright colors, cleaning the room regularly, and making standard operating procedure (SOP) for in-patient room maintenance. Keywords: Air physical environment, microba rate, hospital